Perceptions on The Implementation of Information Services in Class XI High Schools in Bayah District, Lebak Banten Regency - Nurmawati, Nurmawati; Sri Widodo, Rahmi Mellynia (Syntax Corporation, 2023)
This research is expected to help Guidance and Counseling Teachers know students' perceptions of BK services provided in schools. This research is a quantitative descriptive study with a population of 612 students of class XI at the senior high school level in the Bayah District. The sample taken in this study was 242 students. The instrument in this study was a questionnaire on students' perceptions of information services which consisted of 52 statement items. The results of the research as a whole show that students' perceptions of the implementation of information services in high school level schools in Bayah District, obtained students who have perceptions in the very low category as much as 7.4%, the low category as many as 16.9%, the medium category as much as 52.5%, the high category as many as 17.4 % and very high category as much as 5.8%. Based on this, it is concluded that most students have a moderate perception of the implementation of information services in schools, as much as 52.5%.